O que faz uma psicologia social?: em estudo exploratório sobre os significados de intervenção na psicologia social brasileira - Leidiane Pereira Lopes (2013)
Theme identified as central since the first ABRAPSOs propositions, the intervention has been consolidating, in brazilian social psychology, in a field very diversified regarding its objectives, audience and procedures. However, there are few available sources that intended to offer more systematic information about this diversity comprehensiveness and its possible implications for the field. In this sense, the present research aimed to identify and analyze what was considered intervention in 260 complete academic works published in the annals of Brazilian Association of Social Psychology (ABRAPSO) National Meetings that happened in 2007, 2009, 2011. The criterion of selection for the corpus composition was the presence of the word intervention in, at least, two phrases along the report. Two procedures were used to data treatment: Content Analysis and Lexical Analysis (with the aid of ALCESTE software). The Content Analysis allowed us indentify the most generic features from the activities described, such as type of work, objectives, main target, spaces/locals and methodological aspects. The Lexical Analysis enabled the identification of four classes of reduced forms, named why intervene, where intervene, how not to intervene and ways to intervene. The integrated discussion of the achieved results, considering history aspects of social psychology, allowed our construction of a general concept assigned to the term intervention and used at the corpus, as well as an initial mapping of characteristics that enabled to comprehend the related activities set since maintenance and differentiation criteria related to the ABRAPSOs initial propositions.